Occurrence of Polychlorinated Dibenzo-p-Dioxins and Dibenzofurans and Polychlorinated Biphenyls in Fruit and Vegetables from the “Land of Fires” Area of Southern Italy - Mauro Esposito (Toxics, 2017)
The concentrations of polychlorinated dibenzo-p-concentrations dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs) (PCDD/Fs), and polychlorinated biphenyls (PCBs) were determined in fruit and vegetables collected in farms located in the well-known “Land of Fires” area of Southern Italy, in an effort to learn more about the environmental pollution of this high-risk area due to illegal waste dumping and uncontrolled burning near cultivated fields. Concentrations were in the range 0.011–2.26 ng g−1 for the six “indicator” non-dioxin-like PCBs (NDL-PCBs), and 0.0009–0.096 pg WHO toxic equivalent (TEQ) g−1 for the sum of dioxin-like PCBs (DL-PCBs) and PCDD/Fs. Lacking maximum limits for these contaminants in fruit and vegetables, the concentration values found were compared with the action levels set out in the EU Recommendations. These levels were never exceeded in the examined samples. In the present study, the highest mean value for PCDD/Fs + DL-PCB corresponded to apricots, olives, and nuts, while the lowest values were observed in endive and green beans. The results showed also that NDL-PCB levels in apricots were much higher than in any other food, suggesting that they can accumulate PCBs: this fruit might be proposed as a “sentinel” of the presence of these contaminants in the environment.